HUBUNGAN KARAKTERISTIK SOSIODEMOGRAFI DENGAN HEALTH BELIEF PENGGUNAAN KONDOM PADA WANITA PEKERJA SEKS KOMERSIAL (PSK) - Rahmatia; Yosi Maria Wijaya; Susanti Niman (Sekolah Tinggi Ilmu Kesehatan Santo Borromeus, 2022)
The data found that female sex workers with a lifespan of 20 to 30 years say do not use condoms during sexual intercourse and do not believe that condoms can prevent sexually transmitted diseases. Behaviors of using condoms among female sex workers can be seen with a health belief approach. This study aims to determine the relationship of sociodemographic characteristics and health beliefs in condom use among female sex workers. Health belief is a concept that expresses the reason of the individual willingness to do healthy behaviors. This study used cross sectional design in 60 female sex workers. Sociodemographic data analysis using frequency distribution, bivariate analysis using Chi-square test. The results show 70.0% of respondents classified as early adulthood, 53.3% respondents had primary education, 65.0% respondents had low an income, 68.3% respondents were married, and 55. 0% of respondents have a low health belief of condom use. Based on statistical analysis showed that there was no significant relationship between age and income with the health belief of condom use (p = <0.05). The researcher give an agency to provide counseling care.